Pengaruh Transformasi Digital terhadap Loyalitas Nasabah dengan Kepuasan Nasabah sebagai Variabel Intervening pada PT. Prudential Cbd Medan Polonia - Winda Amanda Sari; Fauzi Arif Lubis; Tri Inda Fadhila Rahma (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This research is motivated by the shift in insurance usage culture from conventional to digital, which poses a challenge for insurance companies such as PT. Prudential Syariah in improving the quality of digital marketing services to maintain customer loyalty. Digital transformation not only simplifies transactions but also plays a role in increasing customer satisfaction. This research uses a quantitative method with an explanatory research approach conducted at PT. Prudential CBD Medan Polonia. Data were collected through questionnaires from 376 respondents selected using a purposive sampling technique. The research variables include digital transformation as the independent variable, customer satisfaction as the moderating/intervening variable, and customer loyalty as the dependent variable. Data analysis used linear regression. The results show that digital transformation has a positive and significant effect on customer loyalty. In addition, customer satisfaction also has a positive and significant effect on customer loyalty. Mediation testing shows that customer satisfaction is able to positively mediate the effect of digital transformation on customer loyalty. These findings emphasize the importance of optimizing digital services in increasing customer satisfaction and loyalty in the Islamic insurance industry.